COMP-angiopoietin-1 recovers molecular biomarkers of neuropathy and improves vascularisation in sciatic nerve of ob/ob mice. - Joanna Kosacka; Marcin Nowicki; Nora Klöting; Matthias Kern; Michael Stumvoll; Ingo Bechmann; Heike Serke; Matthias Blüher (PLoS ONE, 2012)
BACKGROUND: Leptin-deficient ob/ob mice are a model of type 2 diabetes induced peripheral neuropathy. Ob/ob mice exhibit obesity, insulin resistance, hyperglycaemia, and alterations of peripheral nerve fibres and endoneural microvessels. Here we test the hypothesis that cartilage oligomeric matrix protein (COMP)-Ang-1, a soluble and stabile form of Ang-1 which promotes angiogenesis and nerve growth, improves regeneration of nerve fibres and endoneural microvessels in ob/ob mice. METHODS AND FINDINGS: COMP-Ang-1 (100 ng/ml) or NaCl were intraperitoneally (i.p.) injected into male (N = 184), 3-month old, ob/ob or ob/+ mice for 7 and 21 days. We measured expression of Nf68, GAP43, Cx32, Cx26, Cx43, and TNFα in sciatic nerves using Western blot analysis. To investigate the inflammation in sciatic nerves, numbers of macrophages and T-cells were counted after immunofluorescence staining. In ultrathin section, number of myelinated/non-mylinated nerve fibers, g-ratio, the thickness of Schwann cell basal lamina and microvessel endothelium were investigated. Endoneural microvessels were reconstructed with intracardial FITC injection. Treatment with COMP-Ang-1 over 21 days significantly reduced fasting blood glucose and plasma cholesterol concentrations compared to saline treated ob/ob mice. In addition, COMP-Ang-1 treatment: 1) up-regulated expression of Nf68 and GAP43; 2) improved expression of gap junction proteins including connexin 32 and 26; 3) suppressed the expression of TNFα and Cx43 and 4) led to decreased macrophage and T-cell infiltration in sciatic nerve of ob/ob mice. The significant changes of sciatic nerve ultrastructure were not observed after 21-day long COMP-Ang-1 treatment. COMP-Ang-1 treated ob/ob mice displayed regeneration of small-diameter endoneural microvessels. Effects of COMP-Ang-1 corresponded to increased phosphorylation of Akt and p38 MAPK upon Tie-2 receptor. CONCLUSIONS: COMP-Ang-1 recovers molecular biomarkers of neuropathy, promotes angiogenesis and suppresses inflammation in sciatic nerves of ob/ob mice suggesting COMP-Ang-1 as novel treatment option to improve morphologic and protein expression changes associated with diabetic neuropathy.